Anesthetic Effects of a Mixture of Medetomidine, Midazolam and Butorphanol in Two Strains of Mice - Kirihara, Yumiko (Japanese Association for Laboratory Animal Science, 2013)
The combination of ketamine and xylazine is a widely used anesthetic for laboratory animals. However, due to an abuse problem in Japan, ketamine has been specified as a narcotic since 2007. Instead of using ketamine, Kawai et al. reported an injectable formula with an equivalent effect to the mixture of ketamine and xylazine [11]. The mixture of 0.3 mg/kg body weight (b.w.) medetomidine (Med.), 4.0 mg/kg b.w. midazoram (Mid.), and 5.0 mg/kg b.w. butorphanol (But.) produced an anesthetic duration of around 40 min in outbred ICR mice. However, the anesthetic effect of the mixture for inbred mice strains remains unknown. Therefore, we examined anesthetic effects of the mixture of Med., Mid., and But. in the BALB/c and C57BL/6J strains. After intraperitoneal injection into mice, right front paw, left hind paw, and tail pinch reflexes as well as corneal and righting reflexes were observed. Every 5 min, we scored each reflex category as 0 for reaction or 1 for no reaction. As long as the total score was at least 4 out of 5, we considered the mixture as putting a mouse in a surgical anesthetic state. The mixture produced an anesthetic duration of more than 45 min in both strains of mice. These results indicate that the mixture of Med., Mid., and But. can be a useful and effective anesthesia for the BALB/c and C57BL/6J strains of inbred mice as well as outbred ICR mice.